Coeliac patients detected during type 1 diabetes surveillance had similar issues to those diagnosed on a clinical basis. (13th January 2017) - Laitinen, Anna U.; Agardh, Daniel; Kivelä, Laura; Huhtala, Heini; Lähdeaho, Marja‐Leena; Kaukinen, Katri; Kurppa, Kalle
Abstract: Aim: Screening children with type 1 diabetes for coeliac disease is controversial, because they often appear asymptomatic. Our aim was to establish whether active screening should be recommended. Methods: This study focused on 22 children whose coeliac disease was detected by serological screening during diabetes surveillance and 498 children diagnosed because of a clinical suspicion. We compared the clinical and histological data at diagnosis and the children's adherence and responses to a gluten‐free diet. Results: The serological screening group suffered less from decreased growth (p = 0.016) and clinical symptoms (p < 0.001) at diagnosis than the clinical group. The groups did not differ in terms of age at diagnosis (p = 0.903), gender (p = 0.353), anaemia (p = 0.886), endomysial antibody titres (p = 0.789) and the severity of small‐bowel mucosal atrophy (p = 0.104). They also showed equal adherence (p = 0.086) and clinical responses (p = 0.542) to a gluten‐free diet after a median follow‐up of 13 months. Conclusion: Coeliac patients detected during diabetes surveillance had signs of malabsorption and advanced mucosal damage that was similar to those diagnosed on a clinical basis. They often suffered from unrecognised gluten‐dependent symptoms and showed excellent adherence and responses to a gluten‐free diet. Our findings support active screening for coeliac disease in patients with type 1 diabetes. Abstract :